Solución de ecuaciones
Enviado por anyelo8490 • 26 de Junio de 2013 • Tarea • 1.681 Palabras (7 Páginas) • 277 Visitas
1. Lim X² -16 = Lim (X - 4) (X + 4) = Lim (X + 4)
X→ 4 X – 4 X→ 4 (X – 4) X→ 4
= 4+ 4 = .8.
2. Lim (X - 1) (X + 1) = Lim (X - 1) (X + 1) = Lim (X - 1) (X + 1) = (1) + 1 = .1.
X→ 1 1 - X² X→ 1 (-X +1) (X + 1) X→ 1 (X - 1) (-X -1) -(-1-1)
3. Lim X (X - 4) = Lim X (X - 4) = Lim X (X - 4)
X→ 0 X² - X+ 2X X→ 0 X(X-1 + 2) X→ 0 X (X + 1)
= Lim X - 4 = 0 - 4 = - 4
X→ 0 X +1 0 + 1
4. Lim X² - 1 = Lim (X² - 4) = Lim - (X - 2) (X + 2)
X→ 2 -2 + X X→ 2 (X – 2) X→ 2 (X - 2)
= Lim - (X + 2) = - 4
X→ 2
5. Lim X² - 1 = Lim (X - 1) (X + 1) = Lim X - 1
X→ 1 X +1 X→ 1 (X + 1) X→ 1
Lim 1 – 1 = 0.
6. Lim X² - 2X + 1 - X² - 1 = - 2 X = -2 (16) ____
X→ 16 2(X - 1) – 2 X + 2 2 (X-1) – 2X + 2 2 (15) – 2 (16) +2
= -32 =
0
...